Analysis of Diazepam Residue from Water Samples by Triple Phase-Suspended Droplet Microextraction Coupled to High Performance Liquid Chromatography and Diode Array Detection - Es'haghi, Zarrin; Bandegi, Sanaz; Daneshvar, Leili; Salari, Poone (Asian Journal of Chemistry, 2010)
New pre-concentration technique, triple phase suspended droplet microextraction (SD-LPME) and liquid chromatography-photodiode array detection were applied to determine diazepam in water samples. The analyte was extracted from 4.5 mL sample volumes directly into 10 μL of extraction solvent. The microextraction process is consisted of a free suspended micro droplet of an aqueous solvent which is delivered to the surface of an immiscible organic solvent. After the optimized extraction time, the suspended micro-droplet is withdrawn by a HPLC microsyringe, injected to and analyzed by HPLC-DAD. The effective parameters such as organic solvent, pH, extraction time, micro droplet volume and agitation speed were investigated. Method was evaluated and enrichment factor 839.8, linearity range from 25 to 5000 ng mL-1 with an average of relative standard deviation (n = 5) 5.62 % for diazepam using a photodiode array detector were determined. All experiments were carried out at room temperature.